Harmonisation Method of Safety Validation Systems - Tarnai, Géza (Communications - Scientific letters of the University of Zilina, 1999)
This paper presents methods to harmonize different safety validations, which were created at different times and by different prescriptions, with each other and with the CENELEC standards, in connection with a concrete application example, the realization of the first electronic interlocking system of the MÁV.